Sacred Light : Holy Places in Louisiana - Meek, A. J. (Book collections on Project MUSE., 2010)
Renowned photographer A.J. Meek takes the novitiate on an inspired visual journey with eighty-eight color photographs of the interiors of churches and synagogues located in south Louisiana, mostly along the lower Mississippi River valley. Tourists may crowd the famous European cathedrals such as Notre Dame in Paris and Westminster Abbey in London. Yet the splendors of local churches in America all too often remain cloistered and unheralded. Meek's beautiful photographs correct this oversight for Louisiana, a state that features a great many beautiful and long-standing holy places. Often incor.